2015
DOI: 10.15376/biores.10.2.3520-3530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Temperature on Properties of Starch-based Adhesives

Abstract: Starch-based adhesives were developed by hydrolyzing starch with polyvinyl alcohol under alkaline and acidic conditions at various treatment temperatures. The chemical and physical structures of the corn starch and hydrolyzed starch were characterized with Fourier Transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), and scanning electronic microscopy (SEM). Thermal degradation and bond strength were also evaluated. The results indicated that the bond strength of starch adhesives reached a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Starch is a carbohydrate polymer derived from the organs, such as roots, tubers, seeds, and fruits of various botanical sources, for example cassava, potato, yam, corn, beans, peas, unripe pawpaw, and banana. It is a highly abundant, renewable, and biodegradable polymer and acts as a source of energy for these plants . Starches are known as polysaccharides because they consist of polymers of d ‐glucose, the basic unit of starch (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is a carbohydrate polymer derived from the organs, such as roots, tubers, seeds, and fruits of various botanical sources, for example cassava, potato, yam, corn, beans, peas, unripe pawpaw, and banana. It is a highly abundant, renewable, and biodegradable polymer and acts as a source of energy for these plants . Starches are known as polysaccharides because they consist of polymers of d ‐glucose, the basic unit of starch (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…It also showed that structure and elasticity of the cassava starchbased is being destroy when temperature increasing to 140 o C. Uthumporn et al [3] stated that different starches have different gelatinization temperature and while the starch under alkali and acid treatment with increasing temperatures could influence gelatinization temperature of starch. According to Yu et al [4], granules morphological changes is effected by heating temperature than compared with heating time, while increase in alkali concentration, gives a strong impression on the swollen granules than neutral and acid conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, bar graph showed fluctuation when cassava starchbased adhesive in plywood increased with hot press temperature, bond strength decreased first, then increased again. Yu et al [4] mentioned that treatment temperature of starchbased adhesive was increased and bond (shear) strength of starch-based adhesive between veneers also increased first, and then decreased in bond strength. This is because of the amount of free hydroxyl groups was presented on starch molecular chain.…”
Section: Methodsmentioning
confidence: 99%
“…5 Starch is made up of two molecules: amylose and amylopectin. Amylose consists of long helical chains, and amylopectin has a branched structure.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%